How Does Electronic Word of Mouth (E-WoM) and Price Affect Purchasing Decisions? - Aprianti, Deva; Avianti, Widiya (Innovation Business Management and Accounting Journal, 2023)
This study aims to determine the electronic word of mouth that becomes a purchase decision for Shopee application users, by involving price variables that affect purchase decisions in Shopee application users. The sampling technique uses probability sampling with a sample of 284 people. Data collection techniques use questionnaires that have been tested for validity and reliability. The data analysis technique used to answer the hypothesis is partial and multiple regression analysis.  Electronic word of mouth influences purchasing decisions, price affects purchasing decisions. The indicator in the price variable that most influences the purchase decision is the competitive price indicator. The better or higher the electronic word of mouth, the decision to visit consumers will also be higher, and vice versa if the electronic word of mouth is lower, then the decision to visit consumers will also be lower. If the company is able to create positive electronic word of mouth among the public, it will increase the number of purchases for the company. Likewise, price affects purchasing decisions in deciding to buy products at Shopee online shopping.